Perubahan Kepemimpinan Idela di Era Kecanggihan Teknologi Sosial Media - Putri, Lestari Perdana; Aslami, Nuri (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The purpose of this research is to find out the ideal leadership change in the era of rapid technological sophistication, to find out how leadership changes in using social media to get closer to members, and also to become one of the requirements in completing courses from Change Management. Qualitative descriptive as method support in completing this research. Regarding data collection techniques using library research collection techniques. The results of this study indicate that social media in terms of its users can bring big changes. Social media also helps leaders create extraordinary ideas that result in good changes that can increase employee performance motivation and benefit all members in a company or organization. A leadership spirit is needed for a leader in the sense of having the intelligence to face the obstacles to existing changes, creating better changes, a soul that can keep up with changing times, a soul who understands changes in technological sophistication. Technology is a symbol of progress. One will not miss anything when he holds a technology.